2019
DOI: 10.3390/molecules24061146
|View full text |Cite
|
Sign up to set email alerts
|

Physalis peruviana-Derived 4β-Hydroxywithanolide E, a Novel Antagonist of Wnt Signaling, Inhibits Colorectal Cancer In Vitro and In Vivo

Abstract: Deregulation of the Wnt signaling pathway leads to colorectal cancer progression. Natural dietary compounds serve as promising candidates for development as chemopreventive agents by suppressing the Wnt/β-catenin signaling pathway. Physalis peruviana-derived 4βHWE showed a significant inhibitory activity with a calculated IC50 of 0.09 μΜ in a screening of novel inhibitors of Wnt signaling with the dual-luciferase reporter assay. This study investigated the anti-tumor effect of 4βHWE and the potential Wnt signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 32 publications
0
23
0
1
Order By: Relevance
“…Ye et al have recently reported that 4β-hydroxywithanolide E (4β-HWE), a natural withanolide from Physalis peruviana increases the level of phosphorylated β-catenin and decreases the levels of active nonphosphorylated form and total β-catenin in colon cancer HCT116 cells ( Ye et al., 2019 ). 4β-HWE has been shown to inhibit cell viability and induce cell cycle arrest at the G0/G1 phase and apoptosis in colon cancer cells with minimal cytotoxicity against normal colonic epithelial cells (CCD-841-CoN) ( Ye et al., 2019 ). More importantly, this compound has shown potent inhibitory effects on tumor growth in mice bearing HCT116 xenograft tumors, without causing significant changes in the average body weights of mice ( Ye et al., 2019 ).…”
Section: Natural Product Inhibitors Of β-Catenin Signaling Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Ye et al have recently reported that 4β-hydroxywithanolide E (4β-HWE), a natural withanolide from Physalis peruviana increases the level of phosphorylated β-catenin and decreases the levels of active nonphosphorylated form and total β-catenin in colon cancer HCT116 cells ( Ye et al., 2019 ). 4β-HWE has been shown to inhibit cell viability and induce cell cycle arrest at the G0/G1 phase and apoptosis in colon cancer cells with minimal cytotoxicity against normal colonic epithelial cells (CCD-841-CoN) ( Ye et al., 2019 ). More importantly, this compound has shown potent inhibitory effects on tumor growth in mice bearing HCT116 xenograft tumors, without causing significant changes in the average body weights of mice ( Ye et al., 2019 ).…”
Section: Natural Product Inhibitors Of β-Catenin Signaling Pathwaymentioning
confidence: 99%
“…4β-HWE has been shown to inhibit cell viability and induce cell cycle arrest at the G0/G1 phase and apoptosis in colon cancer cells with minimal cytotoxicity against normal colonic epithelial cells (CCD-841-CoN) ( Ye et al., 2019 ). More importantly, this compound has shown potent inhibitory effects on tumor growth in mice bearing HCT116 xenograft tumors, without causing significant changes in the average body weights of mice ( Ye et al., 2019 ). Wei et al have found that ethanol extract of Scutellaria barbata D. Don (EESB) inhibits the viability and proliferation of colon cancer HT-29 cells in vitro and suppresses the growth of HT-29 xenograft tumors in vivo ( Wei et al., 2017 ).…”
Section: Natural Product Inhibitors Of β-Catenin Signaling Pathwaymentioning
confidence: 99%
“…In vivo as well as in vitro studies shows that Physalis peruviana-Derived 4-Hydroxywithanolide E-a natural withanolide and umbelliprenin alters the Wnt signaling by reducing the protein expression of Wnt-2, β-catenin, GSK-3β, p-GSK-3β, Survivin and c-myc. It also inhibits the translocation of β-catenin into the nucleus in colorectal and gastric cancer respectively [258]. Silibinin also inhibits the β-catenin levels and its translocation inside the nucleus in colorectal cancer [259].…”
Section: Growth Factor Signalingmentioning
confidence: 99%
“…Previous studies have shown that 4HW has cytotoxic effect against human lung, breast, oral, pancreatic, prostate and renal cancer lines in vitro [24][25][26][27][28] . 4HW also inhibited tumor growth in mouse xenograft models of liver and colorectal cancer 29,30 . Besides anticancer effects, low-dose 4HW exhibits potent anti-inflammatory activity in vitro and in vivo through inhibiting NF-κB or Akt signaling [31][32][33] .…”
mentioning
confidence: 92%